Development of a complex intervention to prevent complications in patients recovering at home after transcatheter aortic valve replacement by optimizing home-based cardiac rehabilitation processes: a Delphi study - Jia, Ying Ying; Guo, Zhi Tin; Zhang, Yu Ping; Song, Jian Ping (Frontiers in Public Health, 2024)
ObjectivesThis study aimed to systematically develop a nurse-led complex intervention to enhance the quality of and adherence to home-based cardiac rehabilitation (HBCR) care for patients who have undergone transcatheter aortic valve replacement (TAVR). The intervention integrated stakeholder perspectives, expert insights, empirical evidence, and theoretical frameworks.MethodsWe initially searched for initial cardiac rehabilitation strategies based on the “Behavior Change Wheel” model and literature review. The Delphi method was used in three rounds of consultations. The guidelines for the Conducting and Reporting of Delphi studies were also followed. The Delphi panel consisted of 15 experts in rehabilitation medicine, clinical medicine, cardiovascular nursing, behavioral science, community nursing, geriatric nursing, and nursing management from various provinces and cities in China. Panelists were asked to rate the effectiveness of HBCR strategies on a 5-point Likert scale.ResultsA questionnaire was sent to the members of the expert panel via email. The consensus from 15 experts led to the development of a framework in round 3. The response rates for the three rounds were 88.23, 100.00, and 100.00%, respectively. The expert authority coefficients for all rounds were 0.95. The Kendall coefficients obtained in the three rounds were 0.09, 0.78, and 0.87, respectively.ConclusionA set of strategies was developed for a comprehensive HBCR program for patients with TAVR, which can provide practical methods for relevant government departments, healthcare professionals, and patients’ families. Future research should investigate the experiences of stakeholders and assess the cost-effectiveness of implementing these strategies.